Pushing the boundaries of self-directed learning: research findings from a study of u.lab participants in Scotland. Issue 6 (2nd November 2018) - Pomeroy, Eva; Oliver, Keira
ABSTRACT: This article reports on the research findings from a qualitative study of adult learners in Scotland taking part in a u.lab MOOC. As a new phenomenon in adult learning, u.lab has been extremely popular yet, at present, there exists little empirical data about either the process or outcomes of the learning experience. This study aims to provide a starting point for further study of u.lab and other emergent trends in adult learning. Here, the accounts of 12 women and men participating in u.lab were analysed using a grounded theory framework. The inductive nature of this approach allowed us to build up a picture of participant experience. Of significance in the findings were participants' relationship to course content, experience of learning in community and engagement in shaping the learning experience. We draw on Illeris' model of the learning field to deepen our understanding of participant experience and to illustrate how the particular constellation of content, incentive and interaction dimensions of learning in u.lab creates a learning space where the possibility for self-direction and self-organisation is extended beyond existing practice.